2013
DOI: 10.5333/kgfs.2013.33.3.197
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Defaunation on In Vitro Fermentation Characteristics and Methane Emission When Incubated with Forages

Abstract: An in vitro study was conducted to determine the effects of defaunation (removal of protozoa) and forage sources (rice straw, ryegrass and tall fescue) on ruminal fermentation characteristics, methane (CH4) production and degradation by rumen microbes. Sodium lauryl sulfate, as a defaunation reagent, was added into the mixed culture solution to remove ruminal protozoa at a concentration of 0.375 mg/ml. Pure cellulose (0.64 g, Sigma, C8002) and three forage sources were incubated in the bottle of culture soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The low total VFA concentration of corn grain could be attributed to its low EDDM. As Qin et al [28] reported, VFA concentration is positively related to EDDM. Furthermore, the diet fed to Hanwoo might have changed the microflora in the rumen.…”
Section: Discussionmentioning
confidence: 89%
“…The low total VFA concentration of corn grain could be attributed to its low EDDM. As Qin et al [28] reported, VFA concentration is positively related to EDDM. Furthermore, the diet fed to Hanwoo might have changed the microflora in the rumen.…”
Section: Discussionmentioning
confidence: 89%
“…3b). Eliminating protozoa from rumen fluid using SDS decreased methane production and increased carbon dioxide production from forage sources [25]. In rumen, protozoa have symbiotic relationships with methanogens.…”
Section: Gas Production During Pretreatment With Rumen Fluidmentioning
confidence: 99%
“…A. cruentus and A. hypochondriacus showed increased pH values, total gas production, and ammonia-N concentration. Finally, the volatile fatty acid (VFA) concentration which reflects the major energy content of the feed or forage as the energy source for ruminants was not affected by different amaranth forages at any incubation time except at 12 h. The A. caudatus showed a higher total VFA concentration than A. cruentus and A. hypochondriacus at 12 h; however, this increase in total VFA concentration was not supported by other fermentation parameters, such as pH, gas production, ammonia-N concentration, and EDDM, which is positively related to VFA concentration [ 31 ]. Regardless of the species of the amaranth forages, the total VFA concentrations of the amaranth forages were all closely comparable with the total VFA concentration of the locally produced forages in Chungcheong province of Korea.…”
Section: Discussionmentioning
confidence: 99%